Risk of hospitalization in synucleinopathies and impact of psychosis - Piat, Capucine; Mullan, Aidan F.; Stang, Cole D.; Hajeb, Mania; Camerucci, Emanuele; Turcano, Pierpaolo; Martin, Peter R.; Bower, James H.; Savica, Rodolfo (Frontiers in Aging Neuroscience, 2023)
Background: Few studies have investigated the risk of hospitalization among patients with synucleinopathies (Parkinson disease, Dementia with Lewy Bodies, Parkinson disease dementia, Multiple System Atrophy) with associated psychosis and the impact of antipsychotic treatments on hospital admissions and duration of the stay.Objective: To determine the risk of hospitalization among patients with synucleinopathies and in patients with associated psychosis. To evaluate the impact of antipsychotic treatments on hospital admission of patients with synucleinopathies and psychosis in an incident cohort study in Olmsted County, Minnesota (MN).Methods: We used the Rochester Epidemiology Project (REP) to define an incident cohort of patients with clinically diagnosed synucleinopathies (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) in Olmsted County, MN. A movement disorder specialist reviewed all medical records to confirm the clinical diagnosis of synucleinopathies using the NINDS/NIMH unified diagnostic criteria.Results: We included 416 incident cases of clinically diagnosed synucleinopathies from 2669 hospitalizations. 409 patients (98.3%) were admitted to the hospital at least once for any cause after the onset of parkinsonism. The median number of hospitalizations for a single patient was 5. In total, 195 (46.9%) patients met the criteria for psychosis: patients with psychosis had a 49% (HR = 1.49, p<0.01) increased risk of hospitalization compared to patients without psychosis. Among patients with psychosis, 76 (39%) received antipsychotic medication. Treatment with antipsychotic medications did not affect the risk of hospitalization (HR = 0.93, p = 0.65). The median length of hospitalization among the entire cohort was 1 (IQR 0 -4) day. There was no difference between hospitalization length for patients with no psychosis and patients with active psychosis (RR = 1.08, p = 0.43) or patients with resolved psychosis (RR = 0.79, p = 0.24).Psychosis increases the risk of hospitalization in patients with clinically defined synucleinopathies; however, it does not affect the length of hospital stays in our cohort. Antipsychotic treatment does not affect the risk of hospitalization in our study.